1997
DOI: 10.1046/j.1365-2036.1997.80252000.x
|View full text |Cite
|
Sign up to set email alerts
|

One‐week low‐dose triple therapy for Helicobacter pylori is sufficient for relief from symptoms and healing of duodenal ulcers

Abstract: SUMMARYAim : To test the hypothesis that 1-week low-dose triple therapy for H. pylori is sufficient for relief from dyspeptic symptoms and healing of duodenal ulcers. Methods : Fifty-nine out-patients with duodenal ulcers and positive rapid urease test participated in this randomized, double-blind, two-centre study. All patients were treated for 1 week with omeprazole 20 mg b.d., clarithromycin 250 mg b.d. and metronidazole 400 mg b.d. In a double-blind fashion, patients were then randomly treated for another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 20 publications
4
35
0
Order By: Relevance
“…These findings are basically in agreement with a recently published randomized double-blind study by Labenz et al [30] showing that continuation of antisecretory drug therapy beyond anti-H. pylori therapy may be unnecessary to achieve rapid symptom relief and reliable healing of uncomplicated duodenal ulcers. In conclusion, combined treatment with OMC for the cure of H. pylori infection in duodenal ulcer patients is significantly more effective than standard dual therapy with OA.…”
Section: Discussionsupporting
confidence: 82%
“…These findings are basically in agreement with a recently published randomized double-blind study by Labenz et al [30] showing that continuation of antisecretory drug therapy beyond anti-H. pylori therapy may be unnecessary to achieve rapid symptom relief and reliable healing of uncomplicated duodenal ulcers. In conclusion, combined treatment with OMC for the cure of H. pylori infection in duodenal ulcer patients is significantly more effective than standard dual therapy with OA.…”
Section: Discussionsupporting
confidence: 82%
“…1 In another study, with a design similar to ours, all 52 patients had an ulcer, which was healed by 28 days, where the H. pylori cure rate was 96%. 2 In our study, as for other studies, the percentage of patients with healed ulcer was no different whether H. pylori was eradicated or not. However, although not significant, there is a tendency to a lower healing rate in patients where eradication failed, as was suggested in another recent study.…”
Section: Discussionsupporting
confidence: 80%
“…However, several studies have suggested that treatment for eradication of H. pylori without prolongation of anti-secretory treatment is sufficient to heal most of the duodenal ulcer. [1][2][3][4][5][6][7][8][9] The present study tests the hypothesis that the 1-week triple therapy for eradication of H. pylori alone is a convenient therapy regimen for uncomplicated H. pylori-associated duodenal ulcer.…”
Section: Introductionmentioning
confidence: 99%
“…5). Among these studies, noteworthy is that performed by Labenz et al [43], in which two therapeutic strategies were randomly assigned: one group of patients received omeprazole, clarithromycin, and metronidazole during 7 days plus a further 3 weeks of omeprazole; the second group received the eradication regimen plus a further 3 weeks of placebo. The ulcer healing rates at 4 weeks were similar (100%) in both groups.…”
Section: Is It Necessary To Prolong Ppi Administration For Duodenal Umentioning
confidence: 99%
“…However, several authors have also achieved very high ulcer healing rates with 'short' eradication therapies using PPI only during 1 week [43][44][45][46][47][48][49][50][51] (fig. 5).…”
Section: Is It Necessary To Prolong Ppi Administration For Duodenal Umentioning
confidence: 99%